The Association Between Depressive Symptoms and Accumulation of Stress Among Black Men in the Health and Retirement Study. Issue 5 (29th September 2020) - Thorpe, Roland J; Cobb, Ryon; King, Keyonna; Bruce, Marino A; Archibald, Paul; Jones, Harlan P; Norris, Keith C; Whitfield, Keith E; Hudson, Darrell
Abstract: Background and Objectives: Among the multiple factors posited to drive the health inequities that black men experience, the fundamental role of stress in the production of poor health is a key component. Allostatic load (AL) is considered to be a byproduct of stressors related to cumulative disadvantage. Exposure to chronic stress is associated with poorer mental health including depressive symptoms. Few studies have investigated how AL contributes to depressive symptoms among black men. The purpose of the cross-sectional study was to examine the association between AL and depressive symptoms among middle- to old age black men. Research Design and Methods: This project used the 2010 and 2012 wave of the Health and Retirement Study enhanced face-to-face interview that included a biomarker assessment and psychosocial questionnaire. Depressive symptoms, assessed by the endorsement of 3 or more symptoms on the Center for Epidemiological Studies—Depression 8-item scale, was the outcome variable. The main independent variable, AL, score was calculated by summing the number values that were in the high range for that particular biomarker value scores ranging from 0 to 7. black men whose AL score was 3 or greater were considered to be in the high AL group. Modified Poisson regression was used to estimate prevalence ratios (PRs) and corresponding 95% confidence intervals (CIs). Results: There was a larger proportion of black men in the high AL group who reported depressive symptoms (30.0% vs. 20.0%) compared with black men in the low AL group. After adjusting for age, education, income, drinking, and smoking status, the prevalence of reporting 3 or more depressive symptoms was statistically significant among black men in the high AL group (PR = 1.61 [95% CI: 1.20–2.17]) than black men in the low AL group. Discussion and Implications: Exposure to chronic stress is related to reporting 3 or more depressive symptoms among black men after controlling for potential confounders. Improving the social and economic conditions for which black men work, play, and pray is key to reducing stress, thereby potentially leading to the reporting of fewer depressive symptoms.